Design and Motion Performance Analysis of a Flexible Wheeled Hopping Robot - Luo Tianhong; Jiang Haiyi; Xue Zan (Jixie chuandong)
In order to improve the adaptive capacity of the robot in a complex environment,solving the problems of the posture adjustments and roll and right itself of the hopping robot,a kind of flexible wheeled hopping robot which adopts flexible wheel train mechanism and the multi-chain hopping mechanisms with the ability of hopping,posture adjustments and roll and right itself is designed. Through control the flexible wheel train mechanism to implement fast moving of the robot on the flat and level road,by using the elastic deformation of flexible wheel to absorb the part impact of the landing when it hits the ground,and the deformation is analyzed which based on the Timoshenko beam theory for the flexible wheel. The robot bounce,takeoff angle adjustment and roll and right itself after landing can be realized by the multi-chain hopping mechanism,and it has the characteristics of single mechanism have multi-function. A kind of composite nut mechanism is designed. The motor of storage energy drive the screw rotation to realize the robot storage energy after the nut is closed. The elastic potential energy of spring release instantaneously when the nut is separated to achieve the hopping motion of the robot. The simulation of the posture adjustment,hopping motion and roll and right itself of robot is carried out by using the ADAMS. A prototype is developed,and the prototype test shows that the design of flexible wheeled hopping robot has the feasibility.